Demand-Driven Skills Training and Results-Based Contracting : Lessons for Youth Employment Programs - World Bank (World Bank, Washington, DC, 2020)
Demand-driven training (DDT) and results-based contracting (RBC) are two mechanisms used to enhance the effectiveness and impact of skill training programs. DDT links skills development explicitly with the job market, typically through employer engagement. Private sector employers define what type of training is necessary, either directly or indirectly through training providers. RBC is based on an agreement with training providers by which the disbursement of funding is conditional on the achievement of defined targets, most often verified gainful employment. Although these two mechanisms are independent, they are frequently combined. Much has been written about various approaches to DDT. However, relatively little is known about the application of RBC in skills training. This report reviews the literature, identifies project examples and derives lessons for the design and implementation of both DDT and RBC. A summary of the existing literature on international experiences with both DDT and RBC, including good practices, is presented here. This review aims to identify the most effective ways to deliver these programs and provide general lessons on their design and implementation. The audience for this review includes World Bank teams and other development and policy practitioners interested in results-based contracting in the context of demand driven training.